Measuring Employee Productivity with AI: Opportunities and Challenges for HR - Sugeng Riyadi; Mohamad Halilintar (Greenation Research & Yayasan Global Resarch National, 2025)
The development of artificial intelligence (AI) technology has revolutionized various aspects of human resource management, including employee productivity measurement. This research explores AI implementation in measuring employee productivity and identifies opportunities and obstacles faced by HR departments. Through a qualitative approach using in-depth interviews and documentation studies, this research involved 15 HR practitioners from various industries in Indonesia. Results show that AI can improve productivity measurement accuracy by up to 67% compared to conventional methods. Main opportunities include evaluation process automation, real-time data analysis, and performance assessment personalization. However, significant obstacles were found in data privacy aspects, employee resistance, and technology implementation complexity. This research provides strategic recommendations for organizations seeking to adopt AI for effective employee productivity measurement.